(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Extra-curricular activities are concurrent with personality development, often named as assumption to pro-social behaviour and analysed considering value orientation. The following hypothesis was set in the study: indexes of expression of pro-social behaviour and value orientation were more characteristic of students involved in extra-curricular activities in comparison with non-active (after school) students. Type of extra-curricular activities was included in the analysis. Research aim. The aim of the study was to analyse relationships between students’ participation in extra- curricular activities and expression of pro-social behaviour as well as their value orientation. Research methods. The sample consisted of 179 students (82 girls and 97 boys) at the age of 16–18 years. Written survey was applied for the research. The participants completed the Pro-social Tendencies Measure (Carlo et al., 2003) and S. H. Schwartz’s (1992) value orientation methodology. Participation in extra-curricular activities was assessed by asking question with a detailed list of structured activities. Research results. Results of the study revealed that there were no links between students’ participation in extra-curricular activities and pro-social behaviour. However, it was determined that public assistance was more characteristic of students participating in artistic extra-curricular activities in comparison to students that attended sports activities after school. The same situation was with value orientation: there was absence of correlations between students’ participation in extra-curricular activities and value orientation, but significant differences related to the type of extra-curricular activities were found. Self-transcendence was more important to students that attended artistic extra-curricular activities in comparison with students participating in sports activities after school. Discussion and conclusion. Tendencies of results of this research are comparable to those in other scientific studies. Studies that examined participation in extra-curricular activities and value orientations of interfaces in Lithuania are still missing. Keywords: value orientation, students’ participation in extra-curricular activities, pro-social behaviour.